Cytologic features of needle aspiration of ovarian sex cord tumor with annular tubules: Report of two cases and literature review. Issue 7 (21st February 2018) - Chen, Xiaowei; Crapanzano, John P.; Gonzalez, Abel A.; Hamele‐Bena, Diane
ABSTRACT: Sex cord tumor with annular tubules (SCTAT) is a rare ovarian tumor with characteristic microscopic morphologic features. Diagnosis most often is based on examination of tissue specimens. Cytologic features of this tumor rarely have been described in the English literature. Herein, we report cytologic findings of cyst aspiration fluid in two cases of SCTAT, with cyto‐histologic correlation.